Representaciones fotográficas en torno a la dictadura en la historiografía argentina reciente - Alberto Del Castillo Troncoso (L'Ordinaire des Amériques)
The political and cultural use of photographs plays a crucial role in the construction of Argentina’s collective memory, especially in the case of the dictatorship (1976-1983). This paper showcases some of the most meaningful analyses recently presented by different Argentinian academics. These texts show how images were created and used to convey the policy of state terrorism initiated by the military officers in power and enforced in several detention and extermination sites.